Ks. abp Henryk Józef Muszyński, Homilia na jubileusz 180-lecia Towarzystwa Miłośników Miasta Bydgoszcz (Kronika Bydgoska, 2010)
The homily for the 180th anniversary of the existence of the Friends of Bydgoszcz Association contains the historical outline of the association and its most important achievements in the service to the city: from the Prussian times to the modem times. The Primate Emeritus says that “Every man, every society has three dimensions: yesterday, today and tomorrow. We go back in our minds to past events to better understand and to feel morę fully our today and to derive from the present moment motives for hope and involvement in the futurę.